Kinerja Keuangan Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Darmansyah Darmansyah (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2015)
This study aimed to evaluate the financial performance of banks in terms of Return on Assets. Besides how big a factor the Capital Adequacy Ratio (CAR) , Loan to Deposit Ratio (LDR), Non Performing Loan (NPL), Operational Cost Ratio (BOPO), Net Interest Margin (NIM) affect the rise and fall of Return on Assets (ROA). Population of this study are bank listed companies in Indonesia Stock Exchange (IDX). Analysis technique of data used multi linear regression of ordinary least square and hypotheses test used t statistic for testing partial regression coefficient and F statistic for testing simultaneous influence at level of significance 5%. This research demonstrated that BOPO) and NPL partially have significant influence negative towards ROA. Then for NIM partially have significant influence positive towards ROA. On the contrary, the CAR and LDR partially have no significant influence towards the ROA. The research also shows that NIM coefficient become largest coefficient values and have the biggest significant influaences. Simultaneously, the CAR, LDR, NPL, BOPO and the NIM has significant influence towards the ROA of Bank companies in IDX.